An ultra-low expansion glue bonding process for MEMS air pressure sensor packaging
The MEMS air pressure sensor packaging process addresses expansion coefficient mismatch by using laser punching, precision adhesive application, and multi-stage curing with phase change materials to enhance sensor stability and reliability under temperature and mechanical stress.
Patent Information
- Application Number
- CN202411035986.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-31
AI Technical Summary
Traditional packaging methods for MEMS pressure sensors face issues with expansion coefficient mismatch and stress concentration due to high expansion coefficients of adhesive materials, leading to performance degradation and failure under temperature and mechanical stress.
A MEMS air pressure sensor packaging process involving laser punching, precision adhesive application, high-pressure extrusion, multi-stage curing, and adaptive phase change materials to ensure uniform adhesive distribution and stability.
The process reduces internal stress and enhances mechanical stability and reliability of the sensor by ensuring uniform adhesive distribution and thermal stability, maintaining performance under varying environmental conditions.
Smart Images

Figure CN118558567B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of MEMS air pressure sensors, and in particular to an ultra-low expansion glue bonding process for packaging a MEMS air pressure sensor. Background Art
[0002] MEMS pressure sensors are widely used in fields such as meteorological monitoring, aerospace, automotive industry, and consumer electronics, which require accurate measurement of air pressure changes. Since the working environment of MEMS pressure sensors is changeable and has high precision requirements, how to ensure the mechanical stability and environmental adaptability of the sensors during the packaging process has become one of the key technical difficulties. Traditional packaging methods often have expansion coefficient mismatch problems when dealing with ambient temperature changes and mechanical vibrations, resulting in sensor performance degradation or failure.
[0003] In the prior art, the packaging of MEMS pressure sensors usually uses adhesive materials with high expansion coefficients. These materials are prone to stress concentration and mechanical fatigue under temperature changes or mechanical stress, which in turn affects the stability and accuracy of the sensor. Common adhesive materials include epoxy resin, polyurethane and silicone, etc., which have large performance differences in high and low temperature environments and are difficult to meet the requirements of high-precision sensors. For example, the epoxy resin used in some sensor packaging processes is easy to soften at high temperatures and may become brittle at low temperatures. These characteristics make it difficult to maintain a stable bonding effect in an environment with large temperature changes;
[0004] However, the existing adhesive materials and packaging processes still have many shortcomings. First, the expansion coefficient of the adhesive is high, which will produce large internal stress when the temperature changes, affecting the mechanical stability of the sensor. Second, the bonding strength of the adhesive is inconsistent in different environments, which can easily cause the sensor to fail under high and low temperature cycles or mechanical vibration conditions, affecting the packaging efficiency and quality.
[0005] Based on this, an ultra-low expansion glue bonding process for MEMS pressure sensor packaging is required. Summary of the invention
[0006] To achieve the above object, the present invention provides the following solution: a MEMS air pressure sensor packaging ultra-low expansion glue bonding process, including the following bonding process:
[0007] Step a, using a laser puncher to form tiny holes with a diameter of 10-50 microns and a depth of 20-100 microns on the bottom surface of the MEMS air pressure sensor chip and the upper surface of the substrate, and the punching density is controlled at 100-300 holes / square centimeter;
[0008] Step b: Clean the bottom surface of the chip and the substrate after the microporous treatment, and use precision dispensing equipment to evenly apply the low expansion adhesive on the bottom surface of the MEMS pressure sensor chip and the upper surface of the substrate. The thickness of the adhesive is controlled at 50-100 microns so that the microporous structure is fully filled with the adhesive. The thickness of the adhesive is calculated as: ,in is the adhesive thickness (micrometers), is the volume of adhesive applied (μl), is the bonding surface area (cm2);
[0009] Step c, placing the MEMS air pressure sensor chip and substrate coated with adhesive in a high-pressure extrusion device, gradually increasing the pressure to 1-2 atmospheres, controlling the flow direction and speed of the adhesive to make it evenly distributed and form a high-density adhesive layer, and the extrusion time is 2 to 5 minutes;
[0010] Step d, after the adhesive is initially cured, add an adaptive phase change material with a phase change temperature of 40-60°C, control the temperature to the phase change temperature of the phase change material, make it undergo phase change, fill the micropores and gaps, the filling time is 5-10 minutes, gradually adjust the temperature to room temperature, and stabilize the phase change material in a solid state;
[0011] Step e, dividing the bonding area into a plurality of small blocks, each of which has an area of 1-2 square centimeters. In each small block, a multi-point temperature monitoring system is used to monitor in real time the temperature changes of each small block in the partitioned progressive multi-stage curing. The multi-point temperature monitoring system is composed of a thermocouple and an infrared temperature sensor. Each small block is provided with 3-5 temperature monitoring points. The temperature is gradually raised from room temperature 25°C to 60°C by gradual temperature increase curing, with each temperature increase of 10°C. The curing time in each temperature stage is maintained for 5-6 minutes, and the curing temperature range is: 25°C≤T≤60°C;
[0012] After each block is cured, the next block is cured in turn, using a partitioned progressive multi-stage curing method until the entire adhesive layer is completely cured;
[0013] Step f, after the partitioned progressive multi-stage curing is completed, the ambient temperature is gradually reduced to room temperature 25°C, the cooling rate is controlled at 1-2°C / minute, the specific range is: 1≤R≤21°C / minute, cooling and stabilization treatment is carried out, and the cooling time is 30-60 minutes.
[0014] Furthermore, the adaptive phase change material is a combination of the following two or three materials, the proportion of each material is controlled between 10%-20% of the total amount, the total amount of the combination is 20%-40% of the weight of the adhesive, and the phase change temperature of the material is between 40-60°C, and the phase change material can fully fill the micropores and gaps at the ambient temperature of use;
[0015] The materials include: polyethylene glycol, paraffin, polyvinyl alcohol, polystyrene, polypropylene, polyurethane, polyamide, polyester, polycarbonate and polymethyl methacrylate;
[0016] The material combination and its proportion are:
[0017] Polyethylene glycol 15%, polyvinyl alcohol 15%, polystyrene 10%;
[0018] Paraffin 20%, polymethyl methacrylate 20%;
[0019] Furthermore, the bottom surface of the chip and the upper surface of the substrate after the micropore treatment of the MEMS pressure sensor are ultrasonically cleaned, the frequency is controlled at 20-40kHz, the cleaning time is 5-10 minutes, and then low-temperature plasma treatment is performed, the power is controlled at 50-150W, and the treatment time is 2-5 minutes;
[0020] The ultrasonic cleaning liquid is deionized water, with 0.1%-0.5% surfactant added, and the cleaning liquid temperature is controlled at 30-40°C.
[0021] Furthermore, in the low-temperature plasma treatment, the plasma equipment adopts radio frequency power control with a frequency of 13.56 MHz, the treatment time is preferably 3 minutes, the gas flow rate is controlled at 20-40 sccm, and the gas used is one of oxygen or argon.
[0022] Furthermore, the formulation of the adhesive comprises the following ingredients:
[0023] Main adhesive base: 60%-80%, curing agent: 5%-15%, plasticizer: 1%-5%, curing accelerator: 0.5%-2%, antioxidant: 0.1%-1%, filler: 5%-15%;
[0024] When the adhesive is applied, the ambient temperature is controlled at 22-25°C and the humidity is controlled at 40-60%.
[0025] Furthermore, in the high-pressure extrusion and flow forming, the pressure change rate of the extrusion equipment is controlled at 0.1-0.5 atmospheres / second to ensure uniform distribution of the adhesive and no bubble formation during the extrusion process.
[0026] Furthermore, in the partitioned progressive multi-stage curing, the curing time of each temperature stage is adjusted to 3-7 minutes according to actual needs. The time is determined by the real-time monitoring of the curing state. The temperature curve is monitored by thermocouples and infrared temperature sensors to ensure the stability of the curing process.
[0027] Furthermore, during the cooling and stabilization, the cooling time is 45 minutes, the ambient humidity is maintained at 50%, and further includes conducting a mechanical property test on the adhesive layer, the test content includes tensile strength, shear strength and peel strength, and the test results must meet the following standards: tensile strength ≥20MPa, shear strength ≥15MPa, peel strength ≥10N / cm.
[0028] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0029] 1. The adjusted pore size and depth of the present invention enable the adhesive to penetrate and fill the microporous structure more evenly, reducing the concentration of internal stress. At the same time, the use of appropriate concentrations of surfactants and low-temperature plasma treatment enhances the adhesion between the adhesive and the substrate surface, improves the tensile, shear and peel strengths of the adhesive layer, and enables the MEMS pressure sensor to maintain high stability and reliability under high and low temperature cycles and mechanical vibration conditions, ensuring the long-term performance of the sensor.
[0030] 2. The present invention achieves uniform distribution and rapid curing of the adhesive layer by optimizing the adhesive formula and high-pressure extrusion parameters. The improved adhesive formula not only has a low expansion coefficient, but also has excellent mechanical properties and thermal stability, and can adapt to the needs of different environmental conditions. The high-pressure extrusion process ensures the full flow of the adhesive under high pressure to form a high-density and uniform adhesive layer. The filling technology of the phase change material further fills the micropores and gaps, enhances the structural stability and heat resistance of the adhesive layer, and effectively avoids stress concentration and adhesive layer damage caused by sudden temperature changes during the curing process through zoned progressive multi-stage curing and appropriate cooling rate, thereby improving the efficiency and quality of the overall packaging process. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a flow chart of the bonding process of the present invention;
[0033] Figure 2 The temperature curve and curing state diagram of the zoned progressive curing of Example 1 of the present invention;
[0034] Figure 3 The temperature curve and curing state diagram of the zoned progressive curing of Example 2 of the present invention;
[0035] Figure 4The temperature curve and curing state diagram of the zoned progressive curing of Example 3 of the present invention;
[0036] Figure 5 The temperature curve and curing state diagram of the zoned progressive curing of Example 4 of the present invention;
[0037] Figure 6 This is a temperature curve and curing state diagram of the zoned progressive curing of Example 5 of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0040] like Figure 1 As shown, a MEMS pressure sensor packaging ultra-low expansion glue bonding process, the specific implementation steps are as follows:
[0041] First, a laser puncher is used to form tiny holes on the bottom surface of the MEMS air pressure sensor chip and the upper surface of the substrate. The laser drilling parameters are set to a hole diameter of 30 microns and a depth of 60 microns. The hole density is controlled at 200 holes / square centimeter. The accuracy and uniformity of the hole size and density are ensured by adjusting the laser power and scanning speed. The purpose is to form a microporous structure on the surface of the chip and the substrate to increase the adhesion area of the adhesive, thereby enhancing the bonding strength.
[0042] Next, the bottom surface of the chip and the upper surface of the substrate after micropore treatment were cleaned. Deionized water was used to clean the surface to remove most impurities, and then ultrasonic cleaning was performed using deionized water with 0.3% surfactant added. The cleaning frequency was 30kHz and the cleaning time was 8 minutes. Ultrasonic cleaning can effectively remove the residues in the micropores and ensure that the surface is free of impurities. Then, low-temperature plasma treatment was performed using radio frequency plasma equipment with a power setting of 100W for 3 minutes. The gas flow rate was controlled at 30 sccm. The gas used was oxygen. The plasma treatment further activated the surface and improved the adhesion of the adhesive.
[0043] Afterwards, a precision dispensing device is used to evenly coat the low expansion adhesive on the bottom surface of the MEMS pressure sensor chip and the upper surface of the substrate. The thickness of the adhesive is controlled at 80 microns. The formula of the adhesive is as follows: 70% main adhesive base, 10% curing agent, 3% plasticizer, 1% curing accelerator, 0.5% antioxidant, and 15% filler. The dispensing process is carried out under the conditions of an ambient temperature of 24°C and a humidity of 50% to ensure the fluidity and uniformity of the adhesive. The adhesive penetrates through the micropores to the surface of the chip and the substrate to form a uniform bonding layer.
[0044] The MEMS air pressure sensor chip and substrate coated with adhesive are placed in a high-pressure extrusion device, and the pressure is gradually increased to 1.5 atmospheres. The flow direction and speed of the adhesive are controlled to make it evenly distributed and form a high-density adhesive layer. The extrusion time is 4 minutes, and the pressure change rate is controlled at 0.3 atmospheres / second. High-pressure extrusion ensures that there are no bubbles in the adhesive and the thickness of the adhesive layer is uniform;
[0045] After the adhesive is initially cured, an adaptive phase change material with a phase change temperature of 50°C is added, specifically a combination of polyethylene glycol (15%), polyvinyl alcohol (15%), and polystyrene (10%). The temperature is controlled to the phase change temperature of the phase change material to make it undergo a phase change and fill the micropores and gaps. The filling time is 8 minutes, and the temperature is gradually adjusted to room temperature to stabilize the phase change material in a solid state. The role of the phase change material is to further fill the micropores and improve the uniformity and stability of the adhesive layer.
[0046] The bonding area is divided into multiple small blocks, and the area of each block is controlled within 1.5 square centimeters. In each small block, a multi-point temperature monitoring system is used to monitor the temperature change in real time. The multi-point temperature monitoring system consists of a thermocouple and an infrared temperature sensor, and 5 temperature monitoring points are set in each small block. The temperature is gradually increased from room temperature 25°C to 60°C by gradual temperature increase, and the temperature is increased by 10°C each time. The curing time in each temperature stage is maintained for 6 minutes, and the curing temperature range is: 25°C≤T≤60°C. After each block is cured, the next block is cured in turn, and a partitioned progressive multi-stage curing is adopted until the entire bonding layer is completely cured. Real-time monitoring and gradual temperature increase curing ensure the uniformity and stability of the curing process.
[0047] After the partitioned progressive multi-stage curing is completed, the ambient temperature is gradually reduced to room temperature 25°C, and the cooling rate is controlled at 1.5°C / minute, with a specific interval of 1≤R≤2°C / minute, for cooling and stabilization treatment, and the cooling time is 45 minutes; the ambient humidity is maintained at 50%, and the bonding layer is further tested for mechanical properties, including tensile strength, shear strength and peel strength. The test results must meet the following standards: tensile strength ≥20MPa, shear strength ≥15MPa, peel strength ≥10N / cm. The mechanical properties test ensures the mechanical properties and stability of the bonding layer;
[0048] according to Figure 2 The temperature curve and curing state diagram of the partitioned progressive curing show the temperature change and curing state during the curing process of Example 1, and clearly show the temperature change process over time and the curing state at different temperature stages.
[0049] The bonding process of this embodiment effectively improves the bonding quality of the MEMS pressure sensor package. The experimental data table shows that all test results meet the expected standards. Especially in the mechanical properties test, the bonding layer exhibits high tensile strength, shear strength and peel strength. The technical solution of this embodiment has significant advantages in improving bonding strength, reducing thermal expansion and ensuring the stability of the bonding layer.
[0050] The difference between this embodiment and embodiment 1 is that:
[0051] The pore size is reduced to 25 microns, the depth is reduced to 50 microns, and the pore density is reduced to 150 holes / square centimeter. The smaller pore size and depth, and lower pore density make the adhesive penetration effect more uniform, reduce the excessive consumption of adhesive, and improve the density and strength of the adhesive layer;
[0052] 0.2% surfactant was used in surface pretreatment, the ultrasonic cleaning frequency was 25kHz, the cleaning time was 6 minutes, the low-temperature plasma treatment power was reduced to 80W, the treatment time was 2 minutes, the gas flow rate was 25 sccm, and argon was used to improve the surface cleanliness and activation effect. The lower concentration of surfactant and argon plasma treatment helped to reduce surface residues and improve the adhesion of the adhesive;
[0053] The adhesive thickness is controlled at 70 microns, the formula ratio is optimized, the dispensing environment temperature is 22°C, and the humidity is 45%. The thinner adhesive layer reduces material costs and optimizes the uniformity and stability of the adhesive layer.
[0054] The high-pressure extrusion pressure is 1.2 atmospheres, the extrusion time is 3 minutes, and the pressure change rate is 0.2 atmospheres / second, which ensures that the adhesive can still form a high-density, bubble-free bonding layer at a lower pressure. The lower extrusion pressure and shorter extrusion time reduce the stress concentration generated during the bonding process, further improving the uniformity and bonding strength of the bonding layer;
[0055] The phase change temperature is 45°C, the phase change material combination is polyethylene glycol (12%), paraffin (15%), and polypropylene (13%), and the filling time is 6 minutes. According to this material combination and filling time, the micropores and gaps can be filled more fully, improving the uniformity and stability of the adhesive layer;
[0056] The partition area is 2 square centimeters, there are 4 temperature monitoring points, the temperature is gradually increased to 55°C, each temperature increase is 8°C, and the curing time is 5 minutes. The larger partition area and the optimized number of temperature monitoring points improve the efficiency of the curing process, while reducing the impact of temperature fluctuations on the adhesive layer, ensuring the uniformity and stability of curing;
[0057] The cooling rate is 1.2°C / min, the cooling time is 40 minutes, the ambient humidity is 55%, and the mechanical properties test standard is slightly lower. The slower cooling rate and shorter cooling time reduce the impact of temperature changes on the bonding layer structure.
[0058] This embodiment 2 not only improves the tensile strength, shear strength and peel strength of the adhesive layer, but also significantly reduces the processing time and energy consumption, and optimizes the bonding process.
[0059] according to Figure 3 The temperature curve and curing state diagram of the partitioned progressive curing show the temperature change and curing state during the curing process of Example 2, and clearly show the temperature change process over time and the curing state at different temperature stages.
[0060] The difference between this embodiment and embodiment 1 is that:
[0061] The pore size is 20 microns, the depth is 40 microns, and the pore density is 200 holes / square centimeter. The smaller pore size and depth make it easier for the adhesive to penetrate and fill the micropores, thereby improving the density and strength of the adhesive layer. At the same time, the moderate pore density ensures sufficient penetration and uniform distribution of the adhesive.
[0062] Using 0.4% surfactant, ultrasonic cleaning frequency 35kHz, cleaning time 10 minutes, low temperature plasma treatment power 120W, time 4 minutes, gas flow 35 sccm, using oxygen, higher concentration of surfactant and higher power plasma treatment helps to thoroughly clean the surface and improve the adhesion of the adhesive;
[0063] The adhesive thickness is 90 microns, the formula ratio is adjusted, the dispensing environment temperature is 25°C, and the humidity is 55%. The thicker adhesive layer provides better mechanical properties. The adjusted formula improves the stability and durability of the adhesive and adapts to different environmental conditions;
[0064] The high-pressure extrusion pressure is 1.8 atmospheres, the extrusion time is 5 minutes, and the pressure change rate is 0.4 atmospheres / second. The higher extrusion pressure and longer extrusion time ensure the full flow and uniform distribution of the adhesive under high pressure, and improve the density and uniformity of the adhesive layer;
[0065] The phase change temperature is 55°C, the material combination is polyethylene glycol (20%) and polyester (15%), and the filling time is 10 minutes. The higher phase change temperature and optimized material combination improve the filling efficiency and stability of the phase change material, and further enhance the structural stability and heat resistance of the adhesive layer;
[0066] The partition area is 1 square centimeter, there are 3 temperature monitoring points, the temperature is gradually increased to 60°C, each time the temperature is increased by 10°C, and the curing time is 7 minutes. The smaller partition area and the reduced number of temperature monitoring points improve the control accuracy of the curing process, ensure the uniform curing of each small block, and improve the efficiency of the curing process;
[0067] The cooling rate is 1°C / min, the cooling time is 30 minutes, the ambient humidity is 60%, and the mechanical performance standard is high. The slower cooling rate and shorter cooling time reduce the impact of temperature changes on the bonding layer structure and improve the mechanical properties and durability of the bonding layer.
[0068] according to Figure 4 The temperature curve and curing state diagram of the partitioned progressive curing show the temperature change and curing state during the curing process of Example 3, and clearly show the temperature change process over time and the curing state at different temperature stages.
[0069] The difference between this embodiment and embodiment 1 is that:
[0070] The pore size is 35 microns, the depth is 70 microns, and the pore density is 250 holes / square centimeter. The larger pore size and depth allow the adhesive to penetrate and fill the micropores more deeply, thereby increasing the density and strength of the bonding layer. The higher pore density ensures the uniform distribution of the adhesive and improves the bonding quality.
[0071] Using 0.3% surfactant, ultrasonic cleaning frequency 30kHz, cleaning time 7 minutes, low temperature plasma treatment power 90W, time 3 minutes, gas flow 30 sccm, using argon, argon plasma treatment enhances the surface activation effect and improves the adhesion of the adhesive. At the same time, the shorter cleaning time and moderate power setting reduce the damage of the surface treatment and maintain the integrity of the substrate;
[0072] The adhesive thickness is 75 microns, the formula ratio is adjusted, the dispensing environment temperature is 23°C, and the humidity is 48%. The thinner adhesive layer provides better mechanical properties and stability. The adjusted formula improves the performance of the adhesive and makes it more adaptable to different environmental conditions;
[0073] The high-pressure extrusion pressure is 1.3 atmospheres, the extrusion time is 4 minutes, and the pressure change rate is 0.25 atmospheres / second. The moderate extrusion pressure and long extrusion time ensure the full flow and uniform distribution of the adhesive under high pressure, and improve the density and uniformity of the adhesive layer;
[0074] The phase change temperature is 50°C, the material combination is paraffin (15%) and polyamide (18%), and the filling time is 7 minutes. The optimized phase change material combination improves the filling efficiency and stability, and further enhances the structural stability and heat resistance of the adhesive layer;
[0075] The partition area is 1.8 square centimeters, there are 4 temperature monitoring points, the temperature is gradually increased to 58°C, each time the temperature increases by 9°C, and the curing time is 6 minutes. The larger partition area and the optimized number of temperature monitoring points improve the control accuracy and efficiency of the curing process, ensuring uniform curing of each small block.
[0076] The cooling rate is 1.3°C / min, the cooling time is 35 min, the ambient humidity is 52%, the mechanical properties standard is high, and the slower cooling rate and moderate cooling time reduce the impact of temperature changes on the bonding layer structure;
[0077] according to Figure 5 The temperature curve and curing state diagram of the partitioned progressive curing show the temperature change and curing state during the curing process of Example 4, and clearly show the temperature change process over time and the curing state at different temperature stages.
[0078] The difference between this embodiment and embodiment 1 is that:
[0079] The pore size is 20 microns, the depth is 40 microns, and the pore density is 250 holes / square centimeter. The smaller pore size and depth, and the higher pore density allow the adhesive to penetrate and fill the micropores more evenly, thereby increasing the density and strength of the adhesive layer and reducing the waste of adhesive.
[0080] The surfactant concentration was 0.5%, the ultrasonic cleaning frequency was 35kHz, and the cleaning time was 9 minutes. The low-temperature plasma treatment power was 110W, the treatment time was 4 minutes, the gas flow rate was 40 sccm, and argon was used. The higher concentration of surfactant and argon plasma treatment further improved the surface cleaning and activation effects and enhanced the adhesion of the adhesive.
[0081] 85 microns. The formula ratio is adjusted to 60% main adhesive base, 15% curing agent, 4% plasticizer, 1.5% curing accelerator, 0.2% antioxidant, and 19.3% filler. The dispensing environment temperature is 24°C and the humidity is 50%. The adjusted adhesive formula improves the mechanical properties and thermal stability of the adhesive layer, adapts to different environmental conditions, and provides better durability and stability.
[0082] The extrusion pressure is 1.4 atmospheres, the extrusion time is 4 minutes, and the pressure change rate is 0.3 atmospheres / second. The moderate extrusion pressure and extrusion time ensure the full flow and uniform distribution of the adhesive under high pressure, thereby improving the density and uniformity of the adhesive layer.
[0083] The phase change temperature is 53°C, the material combination is polyethylene glycol (10%), polycarbonate (20%), and polyester (20%), and the filling time is 9 minutes. The higher phase change temperature and optimized material combination improve the filling efficiency and stability, and enhance the structural stability and heat resistance of the bonding layer.
[0084] Each small block has an area of 1.8 square centimeters and 5 temperature monitoring points. The temperature is gradually increased from room temperature 25°C to 58°C, with a temperature increase of 9°C each time. The curing time in each temperature stage is maintained for 5 minutes. The larger partition area and optimized number of temperature monitoring points improve the control accuracy of the curing process, ensure uniform curing of each small block, and improve the efficiency of the curing process.
[0085] The cooling rate was 1.5°C / min, the cooling time was 45 min, and the ambient humidity was 53%. The moderate cooling rate and cooling time reduced the impact of sudden temperature changes on the structure of the bonding layer and improved the mechanical properties and durability of the bonding layer.
[0086] according to Figure 6 The temperature curve and curing state diagram of the partitioned progressive curing show the temperature change and curing state during the curing process of Example 5, and clearly show the temperature change process over time and the curing state at different temperature stages.
[0087] During the cooling and stabilization process, the mechanical properties of the adhesive layer are tested, including tensile strength, shear strength and peel strength. The standards and calculation methods for each test are as follows:
[0088] Tensile strength test, standard tensile strength ≥ 20MPa, formula: ,in, is the tensile strength (MPa), is the applied tensile force (N), is the cross-sectional area of the specimen (square millimeters, mm²);
[0089] Shear strength test, standard shear strength ≥ 15MPa, formula: ,in, is the shear strength (MPa), is the applied shear force (N), is the shear area of the specimen (square millimeters, mm²);
[0090] Peel strength test, standard peel strength ≥ 10N / cm, formula: ,in, is the peel strength (MPa), is the applied peeling force (N), is the width of the specimen (cm).
[0091] In each embodiment, the bonding layer is cooled and stabilized for 45 minutes, and the ambient humidity is maintained at 50%. The mechanical properties test is then performed, and the specific steps are as follows:
[0092] Tensile strength test:
[0093] Place the sample in a tensile tester and gradually apply tensile force until the sample breaks. Record the maximum tensile force applied. and the cross-sectional area of the sample , calculate the tensile strength And ensure that it is ≥20MPa to verify the anti-destruction ability of the bonding layer in the tensile direction.
[0094] Shear strength test:
[0095] Place the sample in the shear tester and gradually apply shear force until the sample is sheared and damaged. Record the maximum shear force applied. and the shear area of the sample , calculate the shear strength And ensure that it is ≥15MPa to verify the bond layer's ability to resist damage in the shear direction.
[0096] Peel strength test:
[0097] Place the sample in the peel tester and gradually apply peel force until the sample is peeled off and damaged. Record the maximum peel force applied. and the width of the sample , calculate the peel strength And ensure that it is ≥10N / cm to verify the adhesion performance of the adhesive layer in the peeling direction.
[0098] The performance of Examples 1 to 5 was tested below, and the results are as follows:
[0099] According to the test surface, the performance of the MEMS pressure sensor packaging adhesive layer is improved to ensure that it still maintains excellent bonding effect under different environmental conditions. Through the adjusted process, the low expansion coefficient of the adhesive is fully utilized to reduce the internal stress caused by temperature changes and improve the overall performance of the adhesive layer.
[0100] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0101] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A MEMS pressure sensor packaging ultra-low expansion glue bonding process, characterized in that: The following bonding processes are included: Step a, using a laser puncher to form tiny holes with a diameter of 10-50 microns and a depth of 20-100 microns on the bottom surface of the MEMS air pressure sensor chip and the upper surface of the substrate, and the punching density is controlled at 100-300 holes / square centimeter; Step b: Clean the bottom surface of the chip and the substrate after the microporous treatment, and use precision dispensing equipment to evenly apply the low expansion adhesive on the bottom surface of the MEMS pressure sensor chip and the upper surface of the substrate. The thickness of the adhesive is controlled at 50-100 microns so that the microporous structure is fully filled with the adhesive. The thickness of the adhesive is calculated as: ,in is the adhesive thickness, is the volume of adhesive applied, is the bonding surface area; Step c, placing the MEMS air pressure sensor chip and substrate coated with adhesive in a high-pressure extrusion device, gradually increasing the pressure to 1-2 atmospheres, controlling the flow direction and speed of the adhesive to make it evenly distributed and form a high-density adhesive layer, and the extrusion time is 2 to 5 minutes; Step d, after the adhesive is initially cured, add an adaptive phase change material with a phase change temperature of 40-60°C, control the temperature to the phase change temperature of the phase change material, make it undergo phase change, fill the micropores and gaps, the filling time is 5-10 minutes, gradually adjust the temperature to room temperature, and stabilize the phase change material in a solid state; Step e, dividing the bonding area into a plurality of small blocks, each block having an area of 1-2 square centimeters, and in each small block, using a multi-point temperature monitoring system to monitor in real time the temperature changes of each small block in the partitioned progressive multi-stage curing, the multi-point temperature monitoring system is composed of a thermocouple and an infrared temperature sensor, and each small block is provided with 3-5 temperature monitoring points, and the temperature is gradually raised from room temperature 25°C to 60°C by gradual temperature increase curing, and the curing time of each temperature stage is maintained for 5-6 minutes, and the curing temperature range is: 25°C≤T≤60°C; After each block is cured, the next block is cured in turn, using a partitioned progressive multi-stage curing method until the entire adhesive layer is completely cured; Step f: After the partitioned progressive multi-stage curing is completed, the ambient temperature is gradually reduced to room temperature 25°C, the cooling rate is controlled at 1-2°C / minute, and cooling and stabilization treatment is performed. The cooling time is 30-60 minutes.
2. The ultra-low expansion glue bonding process for MEMS pressure sensor packaging according to claim 1 is characterized in that: The adaptive phase change material is a combination of the following two or three materials, each material accounts for 10%-20% of the weight of the adhesive, and the total amount of the combination is 20%-40% of the weight of the adhesive, and the phase change temperature of the adaptive phase change material is 40-60°C, and the phase change material can fully fill the micropores and gaps at the ambient temperature of use; The material combination and its ratio are as follows: Polyethylene glycol 15%, polyvinyl alcohol 15%, polystyrene 10%; Paraffin 20%, polymethyl methacrylate 20%.
3. The ultra-low expansion glue bonding process for MEMS pressure sensor packaging according to claim 1 is characterized in that: The bottom surface of the chip and the upper surface of the substrate after the micropore treatment of the MEMS pressure sensor are ultrasonically cleaned, the frequency is controlled at 20-40kHz, the cleaning time is 5-10 minutes, and then low-temperature plasma treatment is performed, the power is controlled at 50-150W, and the treatment time is 2-5 minutes; The ultrasonic cleaning liquid is deionized water, with 0.1%-0.5% surfactant added, and the cleaning liquid temperature is controlled at 30-40°C.
4. The ultra-low expansion glue bonding process for MEMS pressure sensor packaging according to claim 3 is characterized in that: In the low-temperature plasma treatment, the plasma equipment uses radio frequency power control with a frequency of 13.56 MHz, a treatment time of 3 minutes, a gas flow rate controlled at 20-40 sccm, and the gas used is one of oxygen or argon.
5. The ultra-low expansion glue bonding process for MEMS pressure sensor packaging according to claim 1, characterized in that: The adhesive formulation comprises the following ingredients: Main adhesive base: 60%-80%, curing agent: 5%-15%, plasticizer: 1%-5%, curing accelerator: 0.5%-2%, antioxidant: 0.1%-1%, filler: 5%-15%; When the adhesive is applied, the ambient temperature is controlled at 22-25°C and the humidity is controlled at 40-60%.
6. The ultra-low expansion glue bonding process for MEMS air pressure sensor packaging according to claim 1, characterized in that: In the high pressure extrusion and flow forming, the pressure change rate of the extrusion equipment is controlled at 0.1-0.5 atmospheres / second to ensure uniform distribution of the adhesive and no bubble formation during the extrusion process.
7. The ultra-low expansion glue bonding process for MEMS pressure sensor packaging according to claim 1, characterized in that: In the partitioned progressive multi-stage curing, the curing time of each temperature stage is adjusted to 3-7 minutes according to actual needs. The time is determined by the real-time monitoring of the curing state. The temperature curve is monitored by thermocouples and infrared temperature sensors to ensure the stability of the curing process.
8. The ultra-low expansion glue bonding process for MEMS pressure sensor packaging according to claim 1, characterized in that: During the cooling and stabilization, the cooling time is 45 minutes, the ambient humidity is maintained at 50%, and further includes performing a mechanical property test on the adhesive layer, the test contents including tensile strength, shear strength and peel strength.
